2010
DOI: 10.1002/cncr.25043
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease after nephroureterectomy for upper tract urothelial carcinoma and implications for the administration of perioperative chemotherapy

Abstract: BACKGROUND:The prevalence of chronic kidney disease (CKD) in patients with upper tract urothelial carcinoma (UTUC) is poorly defined, both before and after nephrouretectomy. Although multimodal treatment paradigms for UTUC are under‐developed, this has important implications on patients' ability to receive cisplatin‐based combination chemotherapy (CBCC).METHODS:Estimated glomerular filtration rate (eGFR) was calculated using the Modification of Diet in Renal Disease formula in 336 patients with UTUC, who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(124 citation statements)
references
References 29 publications
(41 reference statements)
4
117
0
3
Order By: Relevance
“…7,8,13,14 Several retrospective studies and the meta-analysis of those studies suggested the efficacy of neoadjuvant chemotherapy in patients with locally advanced or high-grade UTUC. [15][16][17] In patients with node-positive UTUC, only a few retrospective studies reported the impact of preoperative chemotherapy on the oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,13,14 Several retrospective studies and the meta-analysis of those studies suggested the efficacy of neoadjuvant chemotherapy in patients with locally advanced or high-grade UTUC. [15][16][17] In patients with node-positive UTUC, only a few retrospective studies reported the impact of preoperative chemotherapy on the oncological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients can receive chemotherapy because of comorbidity and impaired renal function after radical surgery. Chemotherapy-related toxicity, particularly nephrotoxicity from platinum derivatives, may significantly reduce survival in patients with postoperative renal dysfunction [23,24]. In our case we have bad prognosis.…”
Section: Discussionmentioning
confidence: 63%
“…According to several reports, an estimated 88% to 93% of patients in the post-NU setting have an eGFR <60 and would be ineligible to receive cisplatinbased therapy. 5,11 Although increasing utilization of neoadjuvant chemotherapy for upper tract urothelial carcinoma may partially obviate the importance of ureteral resection in this disease population, these findings retain oncologic importance for several reasons: (1) eligibility for clinical trials; (2) risk for the development of muscle-invasive bladder cancer where chemotherapy is well-established; and (3) lower efficacy of non-cisplatin based palliative chemotherapy. [12][13][14] Segmental resections for upper tract urothelial carcinoma have traditionally been associated with high recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
“…Potential benefits of ureteral resection for the upper tract urothelial carcinoma population may be even more critical due to the inherent incidence of chronic kidney disease following surgery and the potential need for postoperative chemotherapy. 5 Alternatives to NU include endoscopic tumour resections/ablations, segmental ureterectomy (SU), or total ureterectomy (TU) with urinary tract reconstruction. The potential benefits of renal preservation must be weighed against the potential impact of localized urothelial recurrences, which may or may not affect the overall course of the disease.…”
Section: Introductionmentioning
confidence: 99%